Perancangan Antarmuka Pengguna Sistem Informasi Prosedur Pelayanan Umum Menggunakan Metode Design Thinking (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Annisa Mursyidah; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Every institution has standard operating procedures in carrying out operational activities. Standard operating procedures are important to implemented and it is important to be carried out effectively and efficiently because this is an absolute requirement for institution to achieve their vision and mission. Faculty of Computer Science (FILKOM) University of Brawijaya is one of the educational institutions that applies standard operating procedures in the operational process. Standard operating procedures also apply for students. One of the medias that used to deliver these informations to students is through FILKOM's official website. However, it was found that the FILKOM website did not provide a good user experience. The purpose of this study is to propose a solution that can support to solve the problems perceived by students using design thinking. The stages carried out in this study were to dig deeper the problem, analyze the findings data, develop a solution, make a prototype based on solution, and test the user interface. The proposed solution is to add a Service Procedure page to the FILKOMAPPS web apps and create a chatbot for public service procedures. The final results of the study show that the user interface design is in accordance with the desire of the students and proposed solution has been able to support to solve the problems experienced by students.